Internalization of Islamic Values in Tarbiyah Activities for Public Health Students at University of Tadulako, Palu - Kamaruddin Kamaruddin; Mustaqima Mustaqima; Saude Saude (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2022)
The internalization of Islamic values in Islamic education, especially in public universities, has yet to run optimally due to limited learning time. One of the faculties that develop Islamic education learning in non-formal activities is the Faculty of Public Health (FKM) at the University of Tadulako, Palu. Currently, there is phenomena lack of moderate though among university students. Therefore, the researcher intends to identify and analyze the results of internalizing Islamic values in the tarbiyah activities of Faculty of Public Health students at the University of Tadulako in Palu. This study used qualitative paradigm with a phenomenological approach. Data was collected through in-depth interviews, observation, and document analysis. In depth-interview was conducted with ten informants. The data analysis technique uses the matrix style and tests its validity through the triangulation method. Based on the results of the study, it was found that the form of Islamic valyes internalization at the s faculty includes studies of divine values in the form of aqidah values. For example, the consequences of the shahada, then sharia values with practical worship material, knowing Islamic dinul and others. Furthermore, regarding insaniyah values with the topic of study discussing ukhuwah Islamiyah. It was held routinely one to two times a week accompanied by direct practice, namely; reading tests of the Al-Qur'an, Tahsin, thematic and preventive studies. The results aslso show that students internalize Islamic values not only professed in their hearts or verbally, but are proven by realizing divine values and insaniyah values in perfecting their beliefs, sharia, and morals, for example carrying out religious orders, worship properly and behave well with others.